Saudi Arabia : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
The authorities responded quickly and decisively to the COVID-19 crisis and the economy is recovering. COVID-19 cases are well below the 2020 peak and vaccination is progressing. The exit from the remaining COVID-related policy support needs to be carefully managed and the Vision 2030 reform agenda continued.